2018
DOI: 10.3126/janr.v1i1.22225
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse on post-graduate thesis researches of Agronomy Department of IAAS and prioritized future research directions

Abstract: To appraise the major research outputs of agronomic crops and cropping systems and to direct the future research priorities of Agronomy Department of post-graduate (PG) program of Institute of Agriculture and Animal Sciences (IAAS), a rigorous review was accomplished on about two decadal (2000-2018) student’s thesis research works. The review revealed that the agronomic researches at IAAS from 2000 to 2012 were concentrated mostly in on-station farm of Rampur, Chitwan and found their focus on 11 food grain cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is also reported that the changing rainfall pattern and its distribution affect negatively on wheat yield because wheat cultivation is mostly rainfed, but more vulnerable to drought stress than other crops in Nepal (Amgain et al 2019, Amgain and Timsina 2004, 2005Timsina and Humphreys 2006). It is also reported that research on farmers' field would be more vulnerable to climate change and, hence urge for innovative climate change research (Amgain et al 2018;Amgain 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that the changing rainfall pattern and its distribution affect negatively on wheat yield because wheat cultivation is mostly rainfed, but more vulnerable to drought stress than other crops in Nepal (Amgain et al 2019, Amgain and Timsina 2004, 2005Timsina and Humphreys 2006). It is also reported that research on farmers' field would be more vulnerable to climate change and, hence urge for innovative climate change research (Amgain et al 2018;Amgain 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The cereal-based cropping systems in Terai and mid-hills of Nepal are highly intensive, but are facing the sustainability problems due to fragile ecologies and increased dominance of cereals devoid of legumes in the systems (Devkota et al, 2018).The average grain yield of major crop cultivars in any particular region or the whole country is inevitably smaller than yield potential. Preliminary research works in Nepal have shown a large gap between rice yields in farmers' fields (<3.5 t ha -1 ) and on research stations (around 1.5-2.5 t ha -1 ) (Amgain & Timsina, 2005;Dhakal, 2016;Amgain et al, 2018). Maize, the second important crop of Nepal after rice in terms of area accounts 2.2 million tons production with 2.45 t ha -1 productivity (ABPSD, 2017;Shrestha, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These yields are far behind the average world level yield and Nepalese farmers are facing the problems of food insecurity over the years. Central Terai and hills of Nawalpur and Kaski districts being located in central Nepal, the agriculture in these eco-zones is mainly affected by series of climatic anomalies and their induced effects like abiotic and biotic stresses (Amgain & Timsina, 2005) and research on farmers' field would be more vulnerable to climate change and hence urge for innovative research (Amgain et al, 2018). In spite the large research efforts to lift the system yields by various allied sectors of agriculture in these areas; there are still large gaps between biologically and climatically achievable potential yields and research station and on-farm yields and urged for the precision agriculture research like crop simulation modeling (Timsina & Connor, 2001;Timsina et al, 2004;Amgain, 2004).…”
Section: Introductionmentioning
confidence: 99%